Overexpression of IGF2 affects mouse weight and glycolipid metabolism and IGF2 is positively related to macrosomia - Zhang, Qidi; Qin, Shengtang; Huai, Jing; Yang, Huixia; Wei, Yumei (Frontiers in Endocrinology, 2023)
Objective To investigate the effects of insulin-like growth factor 2 (IGF2) on growth and glycolipid metabolism, as well as the underlying mechanism. Methods A mouse model of IGF2 overexpression was constructed to measure weight gain before adulthood, to obtain the values of adult glycolipid metabolism indicators in the peripheral blood and to detect the expression of genes in the IGF2 signaling pathway in different mouse tissues. The present study also explored the independent association between the IGF2 gene and macrosomia by detecting and comparing the expression levels of IGF2 mRNA/H19 RNA in maternal peripheral blood and fetal cord blood of 26 human pregnancies. Results In the mouse model, weights of the IGF2-overexpressing mice were significantly higher than those of the control mice at the age of 5-10 weeks. The glucose concentration, total cholesterol and high-density lipoprotein cholesterol (HDL-C) levels of IGF2-overexpressing mice were significantly lower than those of wild-type (WT) mice. Compared with the WT mice, the expression of H19 was significantly decreased in the pancreas and IGF1R was significantly decreased in the muscle of mice with IGF2 overexpression. The expression levels of STAT3 and AKT2 showed significant decrease in liver, muscle and increase in muscle of IGF2-overexpressing mice, respectively. GLUT2 expression showed significant increase in liver, kidney, muscle and decrease in pancreas of mice with IGF2 overexpression. This study also found that in normal mothers with the similar clinical characteristics, IGF2 expression in the maternal peripheral blood and fetal cord blood is an independent factor influencing macrosomia. Conclusion IGF2 expression was independently correlated with the occurrence of macrosomia, and overexpression of IGF2 significantly increased the weights of mice at the age of 5-10 weeks and significantly affected the values of adult glycolipid metabolism indicators, which might be the result of changes in the IGF2-IGF1R-STAT3/AKT2-GLUT2/GLUT4 pathway. These findings might suggest that IGF2 plays an important role in growth and glycolipid metabolism during both pregnancy and postnatal development.